Equilibrium, kinetics, and thermodynamics of remazol brilliant blue R dye adsorption onto activated carbon prepared from pinang frond - Ahmad, Mohd Azhar; Herawan, Safarudin Gazali; Yusof, Ahmad Anas (Hindawi Publishing Corporation, 2014)
The adsorption of remazol brilliant blue R (RBBR) dye on pinang frond based activated carbon (PF-AC) was investigated in a batch process.Theeffects of initial dye concentration, contact time, solution temperature, and solution pHwere evaluated.The adsorption equilibrium and kinetic were found to follow Freundlich isotherm models and pseudo-second-order kinetic model, respectively. Themechanism of the adsorption processwas found from the intraparticle diffusionmodel.Result fromadsorption thermodynamic show that interaction for RBBR dye was found to be feasible, nonspontaneous, and endothermic.The results indicated that the PFAC is very effective for the RBBR adsorption from aqueous solution.